Aquisições estratégicas: um estudo sobre o mercado de cartões de crédito - Lorey, Vilma Ataíde (2008)
The dynamics of the business world today have caused organizational strategies to adjust to a complex movement marked by globalization, competitiveness and uncertainties. In this context, organizations must seek sustainable alternatives to compete in the market. Among these alternatives, there is a much concern in the implementation of business models focused on strategic brand positioning, partnerships and strategic alliances, and mergers and acquisitions processes, which are used to strengthen the organization in a market in which it already acts or to help enter new markets. In examining the trends of the economy, the financial sector gained prominence due to the increase of credit, heating of the economy, opening of new markets, facilities for communication and information exchange globally. Within the credit card market, the trend of replacing checks with credit cards continues to grow and will remain in the coming years, as plastic money is increasingly more and more popular. Based on this scenario, the goal of this dissertation is to verify as the acquisition process influences the changes in the credit card market and strengthens the position of banks in this industry. To achieve this objective, the research methodology used was a case study of a merger and acquisition process which occurred between two banks that manage credit card issuing. We performed non-structured interviews with the key players who participated in all stages of the process of merger and acquisition. The main conclusion of this work is the confirmation that mergers and acquisitions strengthen the competitive positioning of the banks, which is of course, the primary objective. In the case study, the strategy of buying market share in the premium segment was achieved, in addition to having access to skilled resources and new technologies